Pathogenesis and prevention of placental and transplacental porcine reproductive and respiratory syndrome virus infection - Karniychuk, Uladzimir U; Nauwynck, Hans J (Veterinary research (Paris), 2013)
Porcine reproductive and respiratory syndrome virus (PRRSV)-induced reproductive problems are characterized by embryonic death, late-term abortions, early farrowing and increase in number of dead and mummified fetuses, and weak-born piglets. The virus recovery from fetal tissues illustrates transplacental infection, but despite many studies on the subject, the means by which PRRSV spreads from mother to fetus and the exact pathophysiological basis of the virus-induced reproductive failure remain unexplained. Recent findings from our group indicate that the endometrium and placenta are involved in the PRRSV passage from mother to fetus and that virus replication in the endometrial/placental tissues can be the actual reason for fetal death. The main purpose of this review is to clarify the role that PRRSV replication and PRRSV-induced changes in the endometrium/placenta play in the pathogenesis of PRRSV-induced reproductive failure in pregnant sows. In addition, strategies to control placental and transplacental PRRSV infection are discussed.